Nursing actions to prevent mechanical ventilation pneumonia in the intensive care unit: review - Alex Bezerra da Silva Maciel, Beatriz Santos Sirqueira (Revista de Enfermagem da UFPI)
DOI: https://doi.org/10.26694/2238-7234.6459-64